THE RELATIONSHIP OF STUDENTS’ CORPORATE SOCIAL RESPONSIBILITY ORIENTATION AND ETHICAL PREFERENCES - Harto, Puji; Prastiwi, Andri (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2015)
The objective of this study is to investigate the relationship of ethical preferences with the individual orientation toward corporate social responsibility that covering the economics, legal, ethical, and discretionary aspects. Sample was taken from undergraduate and graduate level accounting students enrolled in the behavioral accounting subject. With the understanding of the corporate social responsibility concept in the subject, it is expected that students can assess the corporate social responsibility orientation based on their behavioral perspective. A number of 195 final respondents were selected. The results from regression analysis show that two types of ethical preferences have significant relationship with the certain aspect of corporate social responsibility orientation. Utilitarianism ethical preference has opposite direction with formalism ethical preference when connected to CSR orientation. While formalism gives the emphasize to legal orientation, utilitarianism gives its opposition toward legal orientation and has positive direction toward economic orientation.Â